Ion-pair reversed-phase chromatography analysis of oligonucleotides using ultra-short (20 x 2.1 mm) columns. Tutorial - Szabolcs Fekete; Mateusz Imiołek; Matthew Lauber (Journal of Chromatography Open)
With this work, we present a comprehensive tutorial for the analysis of oligonucleotides (ONs, 5 to 100 mer) using ion-pair reversed-phase liquid chromatography (IP-RPLC) on ultra-short columns (20 × 2.1 mm). We explore the impact of ion-pairing (IP) agents on ON retention and demonstrate that while IP agents significantly influence absolute retention, their effect on selectivity is often minimal. Our findings emphasize the utility of systematic method development, including software-assisted retention modeling, to optimize gradient steepness and temperature such that resolution can be optimized for both sequence and length variants. We recommend the use of low-adsorption column hardware to minimize nonspecific interactions, which is to the benefit of improving method robustness, peak shapes and recovery (especially of shortmer impurities). Our results confirm the utility of so-called ultra-short column formats as is demonstrated by way of the example, quick run time separations and high-throughput ON analyses. The study establishes practical guidelines for developing robust, reproducible, and high-efficiency IP-RPLC methods for ONs which will be of assistance to analysts working on new therapeutics and new sequencing and diagnostic reagents alike.